Research on the improved method for curling athlete selection - Qi, L.; Miao, Y.; Hou, L. (Boletín Técnico, 2017)
The paper discusses the research on curling athlete selection. Due to the over-reliance on the prediction of the special athletic ability, the traditional selection of special materials has resulted in a low success rate of material selection and even delayed the transference of special categories due to the prediction errors, thus delaying the excavation of athlete's athletic potential, the selection of special materials as a result of the trial to provide a larger space for maneuvering to greatly increase the selectivity of orientation, that greatly improving the success rate of material selection. Therefore, this paper presents the mathematical model based methodology to promote the further performance of the curling athlete selection.